3D convective flow in a hybrid nanofluid filled bi-truncated-pyramid equipped with adiabatic cylinders - Almeshaal, Mohammed A. (Frontiers in Chemistry, 2025)
This study consists of an investigation of the 3D convective flow of hybrid nanofluids (HNFs) within a bi-truncated pyramid equipped with adiabatic cylinders, with a focus on the enhancement of natural convection (NC) heat transfer (HT). The use of HNFs, which is based on the combination of two different nanoparticles (NPs), provides improved thermal conductivity and stability, and leads to significant advantages in thermal management systems. Numerical simulations based of the FEM were performed to analyze the effects of Rayleigh number (Ra), nanoparticle volume fraction (φ), and cylinders size (D) on the heat transfer and fluid flow (FF) within the pyramid. The results showed that at higher Ra and nanoparticle concentrations a significant enhancement of the HT occurs, and the average Nusselt number (Nua) was increased by up to 23% at a Ra = 106 and φ = 0.045. Concerning the adiabatic cylinders, it was found that the optimal cylinder diameter is D = 0.15, (balance between flow disturbance and heat transfer rate). The outputs of the current study are valuable in the optimization of the hybrid nanofluid applications for advanced thermal management solutions.